PROFIL SUMBER DAYA MANUSIA (SDM) GURU PENDIDIKAN JASMANAI OLAHRAGA KESEHATAN (PJOK) DI KABUPATEN PANIAI PROVINSI PAPUA TENGAH - yulin ceyumai; Evi susianti; Dikdik Fauzi Dermawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT Yulince Yumai. Profile Of Physical Education, Health, And Recreation Teacher Human Resources In Paniai Regency, Central Papua Province. Physical Education, Health, And Recreation Study Program, Faculty Of Teacher Training And Education, Singaperbangsa University Karawang. This Study Aimed To Identify And Verify The Number Of Physical Education Teachers Through The Human Resource Profiles Of Physical Education Teachers In Each School, From Elementary, Junior High, To Senior High/Vocational High Schools, And Other Schools In Paniai Regency, Central Papua Province. This Study Used A Qualitative Descriptive Method. Qualitative Description Is A Research Method That Depicts, Describes, And Analyzes Objects In A Specific Situation From All Data Obtained During Fieldwork. The Subjects Were Physical Education Teachers In Paniai Regency, Central Papua Province. The Instrument Used In This Study Was A Questionnaire (Google Search) With Two Aspects: Identifying And Verifying The Number Of Physical Education Teachers In Paniai Regency, Central Papua Province. The Results Of The Study Indicate That The Profile (HR) Of Physical Education Teachers In Paniai Regency, Central Papua Province Has (12) Physical Education Teachers, But From Various Educational Backgrounds, From Sports Education/Formal Education There Are Only (2) Teachers In Paniai Regency, Central Papua Province, (24%) On Average, Physical Education Teachers In Paniai Regency Are very Understaffed. Keywords: Profile of Physical Education Teacher HR.